Situation Report: Romania, 7 December 1970 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Ceausescu to Morocco Romanian Delegation to Warsaw Pact Meeting in East Berlin Communiqué on the Utilization of Flood Relief Funds Economic Relations with Non-Communist Countries Economic Relations with Communist Countries Party Contacts